2017
DOI: 10.2147/ijn.s149235
|View full text |Cite
|
Sign up to set email alerts
|

Improved resection and prolonged overall survival with PD-1-IRDye800CW fluorescence probe-guided surgery and PD-1 adjuvant immunotherapy in 4T1 mouse model

Abstract: An intraoperative technique to accurately identify microscopic tumor residuals could decrease the risk of positive surgical margins. Several lines of evidence support the expression and immunotherapeutic effect of PD-1 in breast cancer. Here, we sought to develop a fluorescence-labeled PD-1 probe for in vivo breast tumor imaging and image-guided surgery. The efficacy of PD-1 monoclonal antibody (PD-1 mAb) as adjuvant immunotherapy after surgery was also assessed. PD-1-IRDye800CW was developed and examined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…They also observed that tumor growth was significantly inhibited in the PD-1-Liposome-DOX-treated group than the IgG control. More recently, the same group published a study that demonstrates the feasibility of using the same PD-1-IRDye800CW-conjugated liposomes for image-guided tumor resection 62 , 63 .…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that tumor growth was significantly inhibited in the PD-1-Liposome-DOX-treated group than the IgG control. More recently, the same group published a study that demonstrates the feasibility of using the same PD-1-IRDye800CW-conjugated liposomes for image-guided tumor resection 62 , 63 .…”
Section: Introductionmentioning
confidence: 99%
“…[24] mAb PD-1-IRDye800CW IRDye800CW NIRF n.a. [25] PD-1/PD-L1 mAb NOTA-α-PD-1 (RMP1-14) NOTA-α-PD-L1 (10F.9G2) 64 Cu PET n.a. [26] mAb Adnectin Df-Nivolumab BMS-986192 89 Zr [ 18 F]AlF PET n.a.…”
Section: Class Substance Namementioning
confidence: 99%
“…The result further demonstrated the feasibility that using PD-1-IRDye800CW to detect PD-L1 expression by fluorescence optical imaging. 60 PAI is usually used for local tissue imaging due to the higher resolution and tissue penetration depth. Liposome-based probes for PAI had be proven the feasibility to guide image tumors.…”
Section: Optical Imagingmentioning
confidence: 99%